The Role of Social Networks in Emergency Management - SMIRNOV, Alexey; BELOZEROVA, Natalia; ALANICHEVA, Natalia; TRUBNIKOVA, Irina; MOTORYGIN, Yuriy (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019DO - 10.14505//jarle.v10.4(42).35, 2019)
The article is focused on the impact of social networks which are becoming increasingly important for information dissemination, user-centered response and efficient coordination between residents and governmental departments at all stages of a disaster. We intend to examine the definition of ‘social network», the most important types of emergency domain-related social media, their functions and benefits. We also propose to investigate the recent activities of the Ministry of Emergencies of the Russian Federation in the sphere of emergency prevention and risk reduction via accessing the social networks pages and assessing their effectiveness.